Development of Educational Game Learning Media for Class VII ICT Subjects at SMPN 1 Wongsorejo - Miftahus Surur; Firman Jaya; Siti Nur Azizah (Journal of Education Technology Information Social Sciences and Health, 2024)
The rapid development of technology as it is today is very influential on the learning process in schools and also affects the learning materials and the way the material is delivered in the process of teaching and learning activities. The use of educational game learning media makes the learning activities carried out not monotonous and can avoid students from feeling bored because students feel involved in learning activities so that students become more active. The purpose of this study was to develop and produce and determine the feasibility of learning media for educational games in ICT subjects for class VII at SMPN 1 Wongsorejo. This study uses research and development methods using the ADDIE model. The author conducted a validation test of material experts, media experts and questionnaires for students to determine the level of feasibility of educational game learning media. From the results of the calculation of the material expert the average value of 29, the assessment is categorized as very good, while the calculation of the media expert has an average value of 26, the assessment is categorized as good and the calculation of the student questionnaire has an average score of 35.75 which is categorized as very good.